Effects of intrauterine retention and postmortem interval on body weight following intrauterine death: implications for assessment of fetal growth restriction at autopsy. (25th October 2016) - Man, J.; Hutchinson, J. C.; Ashworth, M.; Heazell, A. E.; Levine, S.; Sebire, N. J.
ABSTRACT: Objective: According to the classification system used, 15–60% of stillbirths remain unexplained, despite undergoing recommended autopsy examination, with variable attribution of fetal growth restriction (FGR) as a cause of death. Distinguishing small‐for‐gestational age (SGA) from pathological FGR is a challenge at postmortem examination. This study uses data from a large, well‐characterized series of intrauterine death autopsies to investigate the effects of secondary changes such as fetal maceration, intrauterine retention and postmortem interval on body weight. Methods: Autopsy findings from intrauterine death investigations (2005–2013 inclusive, from Great Ormond Street Hospital and St George's Hospital, London) were collated into a research database. Growth charts published by the World Health Organization were used to determine normal expected weight centiles for fetuses born ≥ 24 weeks' gestation, and the effects of intrauterine retention (maceration) and postmortem interval were calculated. Results: There were 1064 intrauterine deaths, including 533 stillbirths ≥ 24 weeks' gestation with a recorded birth weight. Of these, 192 (36%) had an unadjusted birth weight below the 10 th centile and were defined as SGA. The majority (86%) of stillborn SGA fetuses demonstrated some degree of maceration, indicating a significant period of intrauterine retention after death. A significantly greater proportion of macerated fetuses were present in the SGA population compared with the non‐SGA population ( P = 0.01). There was a significant relationship between increasing intrauterine retention interval and both more severe maceration and reduction in birth weight ( P < 0.0001 for both), with an average artifactual reduction in birth weight of around −0.8 SD of expected weight. There was an average 12% reduction in fetal weight between delivery and autopsy and, as postmortem interval increased, fetal weight loss increased ( P = 0.0001). Conclusion: Based on birth weight alone, 36% of stillbirths are classified as SGA. However, fetuses lose weight in utero with increasing intrauterine retention and continue to lose weight between delivery and autopsy, resulting in erroneous overestimation of FGR. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd. Abstract : This article's abstract has been translated into Spanish and Chinese. Follow the links from theabstract to view the translations. This article has been selected for Journal Club. Clickhere to view slides and discussion points.